2018
DOI: 10.1016/j.virol.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of emerging avian reovirus variants isolated from viral arthritis cases in Western Canada 2012–2017 based on partial sigma (σ)C gene

Abstract: Viral Arthritis (VA), a disease caused by Avian Reovirus (ARV), has emerged as a significant cause of economic losses in broiler chicken flocks in Western Canada. These outbreaks were characterized by 4-13% morbidity, followed by a spike in mortality/culling that in extreme cases required total flock depopulation. From 2012-2017, 38 ARV isolates were recovered. Molecular characterization of a partial segment of the sigma (σ)C gene shows all six previously known ARV clusters in Western Canadian broiler chickens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 45 publications
1
44
0
5
Order By: Relevance
“…The strategy of developing a live attenuated vaccine strain by attenuation of FAST protein can also be applied to ARV, which causes arthritis and tenosynovitis in chickens. A recent epidemiological study of ARV in the USA and Canada reported the emergence of antigenic variant strains that are antigenically distinct from the vaccine strain [50,51]. Although single-dose infection with rsMB-ΔFAST did not protect animals effectively, two-dose inoculation completely protected mice from lethal infection.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of developing a live attenuated vaccine strain by attenuation of FAST protein can also be applied to ARV, which causes arthritis and tenosynovitis in chickens. A recent epidemiological study of ARV in the USA and Canada reported the emergence of antigenic variant strains that are antigenically distinct from the vaccine strain [50,51]. Although single-dose infection with rsMB-ΔFAST did not protect animals effectively, two-dose inoculation completely protected mice from lethal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome sequences were aligned using MAFFT v7.450 [ 34 , 35 ], and phylogenetic trees were generated using RAxML v8.2.11. This was possible by applying the nucleotide model GTR+gamma with Rapid bootstrapping and searching for best-scoring ML tree with 1000 bootstrap replicates, with parsimony random seed 400,000 as in previous studies concerning other RNA-viruses [ 36 , 37 , 38 ]. It is worth to mention that selection of this model over others was done based on its high frequency in similar studies, albeit it is expected that different models will lead to very similar results according to Abadi, et al 2019 [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…For phylogenetic analysis on ORF2, 38 aa sequences from CAstV reference strains and field sequences from different locations around the world were retrieved from GenBank and included in the study ( Table 2 ) [ 4 , 5 ]. The CAstV classification based on ORF2 aa sequence was based on two criteria: (1) Bootstrap values of the RAxML phylogenetic trees with 1000 replicates, and (2) percentage of identity matrix resulting from the RAxML phylogenetic tree as in a previous publication based on a different virus, avian reovirus [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the better understanding of the biology of the virus, their variability and the efforts of several groups across the U.S. 5,6,16,17 , Europe 14,18 , Canada 19,20 and China 10 in detecting and typing ARV variants, classical vaccine strains used for immunization of commercial flocks, namely S1133, 1733 and 2408, have not changed since the 1970’s. These strains have proven to be inefficient in controlling the infection, partly due to the RNA virus nature being prone to mutation and recombination events and generating variants that are partially or incompletely protected by antibodies generated by classical vaccine strains.…”
Section: Introductionmentioning
confidence: 99%